Ragam Kuliner Sesaji Dalam Upacara Tradisi di Kabupaten Jepara - Sri Indrahti; Siti Maziyah; Alamsyah Alamsyah (Department of History, Faculty of Humanities, Diponegoro University, 2017)
This article is one of wide studies that analyze culinary food served in cultural activities at Jepara. Those cultural activities become tourist attractions. This study uses qualitative method includes collection of primary and secondary sources such as literature study, observation, structured and in-depth interviews, and Focus Group Discussion (FGD). Historically, cultural activities have been existed during the ancestor period, it is always accompanied by the presence of culinary that has philosophical and historical significance among them. The purpose of this study is to develop culinary culture into business units for the community by combining cultural and tourism market values that have been existed previously. The culinary varieties are expected to be able to contribute in tourism development through the establishment of new business units.